Insiasi Pengembangan Sistem Informasi BUMDes Wunut (SIBUMDes Wunut) untuk Modernisasi Administrasi dan Branding Desa Wisata - Risanda A. Budiantoro; Ummi Nur Laila Sulistyani; Anis Susanti; Febrianur I. F. S. Putra; Athifah Utami (Yayasan Darussalam Bengkulu, 2026)
Digitalization of Village-Owned Enterprise (BUMDes) governance is an urgent need to address the challenges of transparency, accountability, and professionalism in village economic management. The Sumber Kamulyan BUMDes, which manages the Umbul Pelem tourist destination in Wunut Village, still faces obstacles in manual administrative records, the lack of an integrated data management system, and a suboptimal digital branding strategy. This study aims to develop the Wunut BUMDes Information System (SIBUMDes Wunut) as an effort to modernize administrative governance while strengthening the digital branding of the tourism village. The method used is Business Model Canvas analysis to formulate institutional and business strategies, and the application of the Waterfall Model in the system development process, which includes the stages of analysis, design, implementation, and testing. System testing was conducted using blackbox testing to ensure functional suitability. The results show that all key features, such as tourist data management, financial transaction recording, statistical report preparation, and social media content management, can function properly. These findings confirm that SIBUMDes Wunut not only improves administrative order but also serves as a sustainable digital promotion instrument. Thus, this system is declared feasible to be implemented and has the potential to be replicated by other villages as a model for BUMDes digitalization in order to encourage local economic independence.